ESG Communication, Green Marketing Mediation, and Brand Trust in Fore Coffee Indonesia - Chika Agina Hermawan; Mayangsari Alifah Putri; Muhamad Hidayat (Institut Komunikasi dan Bisnis LSPR, 2025)
Purpose. This study examines the effect of ESG communication on brand trust among Fore Coffee Indonesia consumers and investigates the mediating role of green marketing in this relationship, addressing how ESG communication is translated into consumer trust within a local post-IPO food and beverage context. Method. A quantitative explanatory design was used with a purposive survey of 180 Fore Coffee consumers who had recent purchase experience and exposure to the brand’s ESG-related communication. Data were analyzed using a two-stage Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach: Stage 1 generated latent variable scores for lower-order constructs; Stage 2 used those scores to estimate higher-order structural relationships among ESG communication, green marketing, and brand trust. Findings. Results indicate that ESG communication significantly strengthens green marketing practices, which in turn have a strong positive effect on brand trust. The direct effect of ESG communication on brand trust is relatively weak, while the indirect effect through green marketing is significant, confirming green marketing as a key mediating mechanism. Conclusion. ESG communication enhances brand trust primarily when operationalized through credible green marketing practices; sustainability communication alone is insufficient to build consumer trust without consistent implementation in the marketing mix. The study clarifies the mechanism linking ESG communication and brand trust and offers practical guidance for integrating ESG strategies with green marketing execution.